Aggregate Stability Study on Various Land Uses and Land Slopes in Tutur District, Pasuruan Regency, East Java Province, Indonesia - Ahmad Naufal Rusyda; Purnomo Edi Sasongko; Siswanto (JURNAL AGRONOMI TANAMAN TROPIKA (JUATIKA), 2026)
Aggregate stability is an important indicator in assessing soil quality and the potential for land damage due to erosion. Land use that is not in accordance with soil capacity and intensive agricultural activities in sloping areas can reduce the stability of aggregates and increase the risk of soil degradation. This study was conducted in Tutur District, Pasuruan Regency, which has a variety of land uses, including dry fields, apple orchards, coffee plantations, mixed plantations, and natural forests, as well as three classes of slope inclination, namely 8–15%, 16–25%, and 26–45%. The objectives of this study were to examine the aggregate stability index values for various land uses and slope inclinations and to analyze the soil factors that influence these values. The purposive random sampling method was used to determine 45 sample points at soil depths of 0–20 cm and 20–40 cm. The samples were analyzed in the laboratory to obtain data on texture, bulk density, permeability, organic matter (organic C), and aggregate stability index. The data were then analyzed using correlation and linear regression tests to determine relationships among soil physical variables. The results showed that the lowest aggregate stability was found in apple orchards with a slope of 16–25%, while the highest value was found in natural forests with a slope of 8–15%. Organic C and soil texture were recorded as having the greatest influence on the variation in aggregate stability values across all land uses. This finding is a strength of the study because it provides a strong scientific basis for practical recommendations, namely the need to increase organic matter and cover vegetation as a conservation strategy to maintain soil aggregate stability.